The rhizosphere of Phaseolus vulgaris L. cultivars hosts a similar bacterial community in local agricultural soils. - Griselda López Romo; Rosa Isela Santamaría; Patricia Bustos; Francisco Echavarría; Luis Roberto Reveles Torres; Jannick Van Cauwenberghe; Víctor González (PLoS ONE)
This study aimed to investigate the impact of various common beans (Phaseolus vulgaris L.) cultivars on the bacterial communities in the rhizosphere under local agricultural conditions. Even though the differences in cultivation history and physicochemical properties of nearby agriculture plots, the bacterial community in the bulk soil was quite similar and more diverse than that of the rhizosphere. The bacterial community of the rhizosphere was closely similar between Black and Bayo common bean cultivars but differs from Pinto Saltillo common beans collected in a different season. A shared bacterial group within the rhizosphere community across cultivars and specific taxa responding uniquely to each cultivar suggests a balance between responses to soil and plant cultivars. Nevertheless, rhizosphere composition was substantially influenced by the pre-existing soil bacterial community, whose diversity remained consistently similar under the studied field conditions. These findings provide a more comprehensive characterization of the rhizosphere across a limited range of domesticated common beans and agronomic soils that can be expanded to more common bean cultivars and soils to guide appropriate field interventions.